Regulation of G-protein coupled receptor traffic by an evolutionary conserved hydrophobic signal - Angelotti, Tim (2010)
Plasma membrane (PM) expression of G-protein coupled receptors (GPCRs) is required for activation by extracellular ligands; however mechanisms that regulate PM expression of GPCRs are poorly understood. For some GPCRs, such as alpha2c-adrenergic receptors (α(2c)-ARs), heterologous expression in non-native cells results in limited PM expression and extensive endoplasmic reticulum (ER) retention. Recently, ER export/retentions signals have been proposed to regulate cellular trafficking of several GPCRs. By utilizing a chimeric α(2a)/α(2c)-AR strategy, we identified an evolutionary conserved hydrophobic sequence (ALAAALAAAAA) in the extracellular amino terminal region that is responsible in part for α(2c)-AR subtype specific trafficking. To our knowledge, this is the first luminal ER retention signal reported for a GPCR. Removal or disruption of the ER retention signal dramatically increased PM expression and decreased ER retention. Conversely, transplantation of this hydrophobic sequence into α(2a)-ARs reduced their PM expression and increased ER retention. This evolutionary conserved hydrophobic trafficking signal within α(2c)-ARs serves as a regulator of GPCR trafficking.